Asuhan Kebidanan Paripurna Pada Ibu Hamil Risiko Tinggi dengan Anemia - Bherta Yuceline H.S; Estin Gita Maringga; Nunik Ike Yunia Sari (Jurnal Multidisiplin Madani, 2022)
The condition of high-risk pregnant women is a condition that really needs monitoring. The purpose of this case study is to minimize the incidence of complications in Ny. "K" from the third trimester of pregnancy to family planning with continuity of care. This research method uses a case study with the research subject, namely Mrs. "K". Collecting data using interview, observation, and documentation studies. The results of midwifery care carried out on Mrs. "K" with a Poedji Rochjati score of 6. Problems found during pregnancy included frequent urination, edema of the legs, pre-eclampsia, and post-dates. Delivery was performed by cesarean section for postdate and preeclampsia indications. During the puerperium there were complaints of pain from the surgical wound. In the neonate, no problems were found. During the family planning period, the mother chose to use an implant and said there was no problem. Continuity of care is the right care given to pregnant women with high risk because it can help clients in overcoming problems and preventing emergencies and complications.